Primary Non-Hodgkin Lymphoma of the Temporal Bone: Case Report - Trainavičius, Rokas; Sinkevičiūtė, Saulė (Lietuvos chirurgija, 2025)
Lymphomas account for approximately 2.5% of head and neck malignancies, with primary temporal bone involvement being exceedingly rare. The diagnosis of lymphoma, as with other temporal bone malignancies, is often delayed, which adversely impacts both treatment outcomes and overall prognosis. We report a case of a 55-year-old male who presented to our hospital with left-sided facial palsy, unilateral hearing loss, and auricular pain. Biopsies taken during surgical intervention revealed diffuse large B-cell lymphoma infiltrating the mastoid process, external auditory canal, and tympanic cavity. This case underscores the diagnostic challenges posed by temporal bone lymphoma, particularly in presenting symptoms that mimic benign conditions. It emphasizes the importance of considering malignancy in patients with persistent otological symptoms and facial nerve palsy, warranting thorough investigation. Maintaining a heightened level of suspicion for neoplastic disease is crucial until a definitive diagnosis is confirmed. Early detection through comprehensive imaging and biopsy is essential for effective management and improved outcomes.
Keywords: lymphoma; temporal bone malignancies; Non-Hodgkin lymphoma